Level of Anxiety over Future Employment for Final Year Students: A Literature Review - Ibrahim, Isra Dewi Kuntary; Cahyaningrum, Dinis; Hasany, Tifani Dame; Safitri, Dhanny; Asri, Ni Wayan Adelia Mutiara (Journal of Business Management and Economic Development, 2025)
Factors that contribute to the prevalence of college students' anxiety vary, so this study examines and analyzes these factors in college students. The purpose of this study is to determine the factors that contribute to the prevalence of college students' anxiety in general. This research uses a qualitative descriptive literature research methodology, empirical data on which this literature review is based is typically from 2020 to 2024. A systematic review based on PRISMA. Result of this research is students at the final level begin to feel anxiety as a result of anxiety about their future orientation. Excessive fear and concern about future outcomes can inhibit students' desire to participate in their career development, which will worsen their beliefs about the career decision-making process and its potential outcomes. So in this case it is very necessary to have an orientation towards the future, have career maturity and support from parents and teachers has an important role to reduce the level of anxiety felt.